Pesan Moral Dalam Film Merindu Cahaya De Amstel - Siti Fatimatul Munawaroh; Arik Dwijayanto; Teguh Ansori (Journal of Communication Studies, 2023)
Film is one of the mass media that has a function as a medium of information, education, persuasion, and also entertainment. Therefore, film can be used as a medium for conveying moral messages to the public through the scenes shown. The film Missing Cahaya de Amstel is a film with a religious genre with the theme of hijrah which contains many moral messages. This research is a qualitative research using a descriptive approach with semiotic theory. The data collection technique in this study was by means of observation, namely observing and watching every scene of the film Merindu Cahaya de Amstel carefully. Then do documentation in the form of taking pictures by taking screenshots of scenes that are considered to contain a moral message. The data analysis technique in this study uses semiotic analysis in every scene that contains elements of a moral message with the Ferdinand De Saussure Semiotics model. Based on the results of the analysis of the data obtained in this study, it shows that the signifiers and signifieds are found in the scenes in the film Merindu Cahaya de Amstel and contain elements of a moral message. The moral message contained in the film Missing Light de Amstel. First, tolerance with indicators of accepting differences, respecting others, respecting other people's beliefs and allowing or not forcing desires. Second, social care with indicators of mutual help and sympathy as well as empathy or tolerance